ANALISIS KONSENTRASI LOGAM BERAT Pb, Cd DAN KESADAHAN DI PERAIRAN SUB DAERAH ALIRAN SUNGAI (DAS) GARANG, SEMARANG - Mayang Rizkiyah; Siti Rudiyanti; Arif Rahman (Jurnal Pasir Laut, 2021)
The Garang Sub-watershed consists of a reservoir and some river that flows from its upstream to downstream. The changes in water quality that occur upstream will affect the downstream. Garang watershed’s condition is easily contaminated, especially from element Lead (Pb) and Cadmium (Cd). This condition is caused by human activities that can impact the watershed’s water quality. The purpose of this research is to find out Pb’s concentration, Cd’s concentration and its comparison with quality standards, the difference between Pb’s concentration and Cd’s concentration at Garang Sub-watershed’s upstream, Jatibarang Reservoir and Garang Sub-watershed’s downstream, and the correlation of Pb’s concentration and Cd’s concentration to the water hardness as one of the factors that affect heavy metals.The method of this research is surevy method with quantitative descriptive analysis method. The sampling was conducted in 13 stations in September 2020 stations 1-3 were upstream, stations 4-10 were reservoirs and stations 11-13 were downstream. The highest Pb’s concentration was 0,52 mg/l at the 13th station, and the lowest Pb’s concentration was 0,252 mg/l at the 7th station. The highest Cd concentration was 0,116 mg/l at the 1st station and 3rd station, and the lowest Cd concentration was 0,058 mg/l at the 4th station. Based on the regulation (PP. No. 82, 2001), the concentration of heavy metals exceeds the water quality standards (Pb > 0,03 mg/l and Cd > 0,01 mg/l). There is no difference between Pb and Cd concentrations at the upstream, Jatibarang reservoir, and downstream (Sig.>0.05). There are a correlation of heavy metal Pb’s concentration and Cd’s concentration with the water hardness shows a very low correlation, Pb (r = 0.146) and Cd (r = 0.085).